Transcatheter arterial chemoembolization of apatinib and camrelizumab (SHR1210) against liver metastasis from hepatic neuroendocrine tumor: a case report - Qi, Ruobing; Yang, Wenhua; Zhu, Sixian; Mao, Jie; Yang, Bei; Xu, Anhui; Fu, Qiang (Frontiers in Oncology, 2024)
In this case report, we present the case of a 46-year-old woman with a hepatic neuroendocrine tumor (NET G2)-induced liver metastases. Initially, the left lateral lobectomy of the liver was performed. The post-operative pathological examination revealed NET G2, leading to the post-operative recovery with a general review. Further, the re-examination of liver magnetic resonance imaging (MRI) showed post-operative changes in the tumor of the left lateral lobe, with multiple liver masses and possible metastasis. Thus, the liver interventional therapy and apatinib-based targeted therapy based on the "camrelizumab + apatinib" regimen were performed, respectively. The 20-month follow-up indicated a slightly increased hepatic hilum and retroperitoneal lymph nodes, accompanied by hand-foot syndrome. Eventually, the overall condition continued to relieve, indicating that the combined treatment could substantially improve the NET G2 conditions-associated liver metastasis.